Pengaruh Harga dan Reputasi Perusahaan Terhadap Loyalitas Penggunaan Aplikasi Gojek - Muthia Afridita; Rose Rahmidani (Universitas Negeri Padang, 2022)
The purpose of this study was to determine the effect of price and company reputation on loyalty to the use of the Gojek application for students at the State University of Padang. The research method used in this research is descriptive quantitative. The population in this study were students of the State University of Padang. The number of research samples was determined using the Cochran formula as many as 100 people and selected using a non-probability sampling method with a purposive sampling technique. The data used is the type of primary data obtained through distributing questionnaires to Padang State University students with predetermined criteria. The analytical method used is multiple regression analysis using SPSS 20. The results show that (1) Price and Company Reputation have a significant effect on Customer Loyalty, (2) Price has a significant effect on Customer Loyalty, (3) Company Reputation has a significant effect on Customer Loyalty.Keywords: price, company reputation, customer loyalty